Widespread anticoagulant resistance in house mice (Mus musculus musculus) linked to the Tyr139Phe mutation in the Czech Republic - Marcela Frankova; Zuzana Starostova; Radek Aulicky; Vaclav Stejskal (Scientific Reports)
Abstract Despite the widespread use of anticoagulant rodenticides in baits for controlling commensal rodent pests, their application is problematic due to secondary intoxication and increasing resistance. In contrast to studies on Western European house mice (Mus musculus domesticus), few resistance studies have focused on Eastern European house mice (M. musculus musculus), which have a western distribution boundary in the Czech Republic. This study newly analysed the VKORC1 gene in M. m. musculus field populations from Czech farms and grain stores and identified a nonsynonymous mutation Tyr139Phe. This mutation was common throughout the Czech Republic and was present in 80.2% of the 86 individuals sampled. Additionally, all individuals exhibited a genotype with three synonymous mutations specific to the subspecies M. m. musculus. The functional (mortality–survival) response of the Tyr139Phe mutation was validated in a laboratory choice feeding test using bromadiolone-based bait, where all resistant homozygous individuals survived, while all susceptible mice died, with a mean survival of 6.9 days.